TINGKAT KONSUMSI ZAT GIZI DAN STATUS GIZI BERDASARKAN PERSEPSI CITRA TUBUH SISWI DI SMA NEGERI 8 DENPASAR - Vidya Wiswamadanti; Putu Suiraoka; Komang Agusjaya Mataram (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Al Asyariah Mandar, 2022)
Malnutrition and overnutrition are two nutritional issues that Indonesia is now dealing with. Underweight is a common nutritional issue in adolescence. Based on the perceptions of students at SMA Negeri 8 Denpasar towards their bodies, this study seeks to compare the differences between the amount of nutrients consumed and nutritional status. This kind of study uses cross-sectional research design and observational methods. All of the second graders at SMA Negeri 8 Denpasar make up the population, and simple random sampling was used to choose the sample. collecting data for study utilizing primary and secondary sources. Weighing, measuring, and conducting in-person interviews with respondents provided the primary data. Univariate and bivariate analysis with the Mann-Whitney statistical test were the methods used for data analysis in the SPSS software. The findings revealed that out of 97 samples, 52.6% had a negative perspective of their bodies, 77.3% consumed less energy, 69.1% consumed less protein, and 49.5% had nutritional statuses indicative of undernutrition. The study's finding (p=0.002) suggests that there is a correlation between energy usage and perceived body image. The amount of protein consumed and the opinion of one's body image varied (p=0.022). Nutritional state and self-perception of one's physique differ (p=0.002).